Developmental Trajectory of Galloping Skill in Children: A Comparative Age-Based Analysis - Tommy Rizki Prasetyo; Sugiana Sugiana; Ahmad Muchlisin Natas Pasaribu; Rolly Afrinaldi (Journal Coaching Education Sports, 2026)
The development of basic motor skills is an important foundation in supporting physical activity and motor development in early childhood, with one of the locomotor skills being galloping. This study was specifically examined, particularly in observing developmental patterns based on age. The aim was to analyze the developmental trajectory of galloping skills in children aged 5–7 years through an age-based comparative approach. The method used was a quantitative systematic review with reference to the PRISMA guidelines. Data were obtained from reputable scientific articles indexed in Scopus, ScienceDirect, Web of Science, and Google Scholar spanning the years 2011–2026. Of the total 220 articles identified, 12 articles met the inclusion criteria and were further analyzed. Data analysis techniques included descriptive analysis, data standardization, and comparative analysis based on age groups. The results showed that galloping ability increased linearly from 5 to 7 years of age, with mean scores of 8.6, 10.3, and 11.9, respectively. These findings indicate progressive development and an acceleration phase at 5–6 years of age. The novelty of this research lies in the use of a quantitative synthesis approach to identify age-specific trajectories of galloping skill development, a topic rarely studied in depth. The results contribute to the development of assessments and interventions for physical education learning based on early childhood motor development.